PENGARUH SKILL DAN CAPABILITY TERHADAP EFEKTIVAS KERJA KARYAWAN PADA PT. AMARTA MOTOR HONDA KOTA GORONTALO - Husin, Wiwin L.; Muji’zat, Poppy (Universitas Gorontalo, 2023)
AbstractThe research aims to find the effect of skills (X1) and capabilities (X2) on the work effectiveness of the employees at PT. Amarta Motor Honda in the City of Gorontalo. The research uses 45 employees as samples by distributing questionnaires to the respondents, which will then be examined through two stages of test: the validity and reliability test. Then, the result will be continued by conducting the hypnothesis test using the Path Analysis as the analyzing tool. The research applies the Quantitative and the Qualitative method of research.Keywords: skills, capability, work effectiveness.